An Employee Competency Development Strategy To Increase Productivity In The Digital Era - Nyak Surayuddin (Sean Institute, 2024)
The rapid advancements in technology and the digital transformation of indus-tries have necessitated innovative strategies for employee competency development to maintain organizational competitiveness. This study explores the implementation of em-ployee competency development strategies designed to increase productivity in the digi-tal era. Using a qualitative research approach, the study examines case studies from vari-ous industries that have successfully integrated digital tools and training programs into their human resource management practices.The findings reveal that effective compe-tency development strategies involve a combination of personalized training programs, continuous learning opportunities, and leveraging digital technologies such as e-learning platforms and virtual simulations. Moreover, fostering a culture of adaptability and inno-vation among employees was found to be critical in enabling organizations to navigate the challenges of digital disruption. The study concludes that organizations that prioritize employee competency development not only enhance productivity but also improve em-ployee engagement and organizational resilience in the face of rapid technological change. This research provides valuable insights for HR practitioners and policymakers in designing and implementing effective development strategies to meet the demands of the digital era.